Can Preoperative High Resolution Computed Tomography Be Rationalized in Adult Cochlear Implant Candidates?. Issue 10 (December 2018) - Gaskell, Peter; Muzaffar, Jameel; Colley, Steve; Coulson, Chris
Abstract : Objective: To establish whether criteria can be used to identify patients who do not need high resolution computed tomography (HRCT) scans before cochlear implant operations, by retrospectively applying a preoperative selection pathway, the Cambridge Cochlear Implant Protocol (CCIP). Study Design: Retrospective case series. Setting: Tertiary referral center, Queen Elizabeth Hospital, Birmingham, UK (QEHB). Patients: One hundred adult patients receiving primary cochlear implantation (CI) operations from April 2015 to July 2016 performed at the QEHB who received preoperative HRCTs. Main Outcome Measures: Etiology of hearing loss and anatomical abnormalities were collected by reanalyzing HRCT scans. Patients were retrospectively grouped according to criteria to restrict HRCT use derived from the Cambridge Cochlear Implant Programme (CCIP). The two main outcomes, recorded management change and significant abnormalities, were compared between the two CCIP groups, scanned and not scanned. Results: Twenty-six patients had significant abnormalities detected on imaging, 16 in the scanned group and 10 in the not scanned group ( p  = 0.152). Five patients had a recorded management change as a result of HRCT scan, four scanned group, one not scanned group ( p  = 0.107). Significant abnormalities and recorded management change were seen across all etiological subgroups of hearing loss. Conclusion: The anatomy within the temporal bone is variable amongst CI recipients. Recorded management change and significant abnormalities occurred in both CCIP groups and across many etiologies of hearing loss patients. No specific group, based on the etiology of their hearing loss could be identified that do not require preoperative HRCT. Therefore, it is recommended that all CI patients should continue to receive preoperative HRCT imaging.